Target Fishing by Cross‐Docking to Explain Polypharmacological Effects. Issue 7 (1st June 2015) - Patel, Hitesh; Lucas, Xavier; Bendik, Igor; Günther, Stefan; Merfort, Irmgard
Abstract Drugs may have polypharmacological phenomena, that is, in addition to the desired target, they may also bind to many undesired or unknown physiological targets. As a result, they often exert side effects. In some cases, off‐target interactions may lead to drug repositioning or to explaining a drug's mode of action. Herein we present an in silico approach for target fishing by cross‐docking as a method to identify new drug–protein interactions. As an example and proof of concept, this method predicted the peroxisome proliferator‐activated receptor (PPAR)‐γ as a target of ethacrynic acid, which may explain the hyperglycemic effect brought on by this molecule. The antagonistic effect of ethacrynic acid on PPAR‐γ was validated in a transient transactivation assay using human HEK293 cells. The cross‐docking approach also predicted the potential mechanisms of many other drug side effects and discloses new drug repositioning opportunities. These putative interactions are described herein, and can be readily used to discover therapeutically relevant drug effects.